2015
DOI: 10.1016/j.gore.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Delayed and clinically isolated port site carcinosarcoma recurrence as an early indicator of disseminated disease

Abstract: A 71-year-old woman with suspected endometrial cancer underwent robotic-assisted hysterectomy, bilateral salpingo-oophorectomy, pelvic and para-aortic lymph node dissection, and infracolic omentectomy revealing a stage II uterine carcinosarcoma with components of serous adenocarcinoma and undifferentiated spindle cell sarcoma. There was no evidence of distant metastasis at the time of surgery. However pelvic washings were positive for malignant cells. She received adjuvant chemotherapy and vaginal cuff brachyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In our retrospective analysis, we found that PSM in most case reports occurred more frequently in the incision lower abdomen rectus abdominus of bilateral inguinal regions and pubic symphysis. [25][26][27][28] PSM around the umbilicus or epigastrium is rare. 29,30 Whether the puncture point near the tumor is more likely to cause implant metastasis remains unknown and needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…In our retrospective analysis, we found that PSM in most case reports occurred more frequently in the incision lower abdomen rectus abdominus of bilateral inguinal regions and pubic symphysis. [25][26][27][28] PSM around the umbilicus or epigastrium is rare. 29,30 Whether the puncture point near the tumor is more likely to cause implant metastasis remains unknown and needs further study.…”
Section: Discussionmentioning
confidence: 99%